Safety and efficacy of the immunosuppressive agent 6-tioguanine in murine model of acute and chronic colitis - Kverka, Miloslav; Rossmann, Pavel; Tlaskalova-Hogenova, Helena; Klimesova, Klara; Jharap, Bindia; de Boer, Nanne K; Vos, Rene M; van Bodegraven, Adriaan A; Lukas, Milan; Mulder, Chris J (BMC gastroenterology, 2011)
BACKGROUND: Oral thiopurines are effective and widely used in treatment of inflammatory bowel disease (IBD) in humans, although their use is limited due the development of adverse events. Here, we examine the efficacy and toxicity of oral treatment with 6-tioguanine (6-TG) and azathioprine (AZA) in a murine model of IBD. METHODS: We induced acute or chronic colitis in BALB/c mice by one or four cycles of 3% dextran sulphate sodium (DSS), respectively. Mice were treated by daily gavages of various dosages of 6-tioguanine, azathioprine, or by phosphate buffered saline (PBS) starting the first day of DSS or after two cycles of DSS, respectively. We monitored the efficacy and toxicity by measuring the weight change and serum alanine aminotransferase (ALT) activity and by disease severity and histology, at the end of the experiment. Moreover, we measured cytokine production after colon fragment cultivation by enzyme-linked immunoabsorbent assay and numbers of apoptotic cells in the spleen by flow cytometry. RESULTS: 6-TG is effective in the treatment of acute DSS-induced colitis in a dose-dependent manner and 40 μg of 6-TG is significantly more effective in the treatment of acute colitis than both AZA and PBS. This effect is accompanied by decrease of IL-6 and IFN-γ production in colon. We did not observe histological abnormalities in liver samples from control (PBS) or 6-TG treated mice. However, liver samples from most mice treated with AZA showed mild, yet distinct signs of hepatotoxicity. In chronic colitis, all thiopurine derivatives improved colitis, 20 μg of 6-TG per dose was superior. High doses of 6-TG led to significant weight loss at the end of the therapy, but none of the thiopurine derivatives increased levels of serum ALT. Both thiopurine derivatives reduced the proportion of apoptotic T helper cells, but a high production of both IL-6 and TGF-β was observed only in colon of AZA-treated mice. CONCLUSIONS: Use of 6-TG in the treatment of experimental colitis in mice appears superior to AZA administration and placebo. In contrast to 6-TG, the use of AZA resulted in histological liver abnormalities.
Keywords: Models, Animal; kolon; Analysis of Variance; T-lymfocyty pomocné-indukující; Interferon-gamma; Transforming Growth Factor beta; Weight Loss; Colitis; chronická nemoc; thioguanin; Interleukin-6; myši inbrední BALB C; interferon gama; Chronic Disease; Alanine Transaminase; Mice, Inbred BALB C; transformující růstový faktor beta; akutní nemoc; Acute Disease; alanintransaminasa; Animals; Dextran Sulfate; ženské pohlaví; analýza rozptylu; játra; interleukin-6; zvířata; Colon; Thioguanine; azathioprin; myši; apoptóza; modely u zvířat; hmotnostní úbytek; kolitida; Liver; Mice; Female; Azathioprine; Apoptosis; T-Lymphocytes, Helper-Inducer; síran dextranu